2009 IEEE International Conference on Communications 2009
DOI: 10.1109/icc.2009.5199421
|View full text |Cite
|
Sign up to set email alerts
|

RF in the Jungle: Effect of Environment Assumptions on Wireless Experiment Repeatability

Abstract: Most researchers conduct wireless networking experiments in their laboratory or similar indoor environments. Such environments are veritable RF jungles, especially when we consider the ISM bands. In this paper we examine and test several common explicit and implicit assumptions that researchers tend to make about the wireless environment. Although these assumptions are acknowledged by most researchers, the extent of their impact is often underestimated. We find that because the environment is always in flux, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Though we do not directly show, our simulations seem to indicate that multipath effects are not a significant factor in our experiments. Also, studies have shown that radio noise in a typical work environment is very high [8]. Our own measurements (Section 4) confirm this.…”
Section: Additional Notes and Discussion Regarding The Experimentssupporting
confidence: 71%
“…Though we do not directly show, our simulations seem to indicate that multipath effects are not a significant factor in our experiments. Also, studies have shown that radio noise in a typical work environment is very high [8]. Our own measurements (Section 4) confirm this.…”
Section: Additional Notes and Discussion Regarding The Experimentssupporting
confidence: 71%
“…The authors of [126] have identified six components of experimental control that contribute to the overall success of designing an experiment on a WMN testbed. Further, conducting experiments in places where uncontrollable wireless environments (called RF Jungles as coined by the authors in [127]) may lead to misrepresentations. The topology has a tremendous effect on experiments, as distance, physical impediments or obstructions, and even atmospheric conditions can cause variations in wireless communications.…”
Section: Lower Costmentioning
confidence: 99%
“…Most of the time, researchers make simplifying assumptions about the nature of their test environment and the experiment control procedures. However these assumptions do not always hold good [1] making it harder to isolate device/protocol performance from environmental effects.…”
Section: Introductionmentioning
confidence: 98%